2020
DOI: 10.3233/blc-200282
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Field Cancerization in Bladder Cancer

Abstract: BACKGROUND: Morphologically normal tissue, adjacent to tumors, contains multiple molecular changes, the so-called field cancerization. The multifocal and recurrent nature of bladder cancer has been hypothesized to originate from this. However, further studies are required to explore the mutational composition of normal tissue adjacent to tumors. OBJECTIVE: To analyze field cancerization in bladder cancer patients using a non-tumor guided approach. METHODS: We investigated the mutational landscape of normal app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Similar detailed molecular analyses of pathologically normal sections of the bladder from patients with NMI tumors remains scarce, as these patients rarely are subjected to cystectomy. However, Thomsen et al 9 and Strandgaard et al 10 approached the problem by multiple sampling of tumor free regions of the urothelium from bladders with non-muscle invasive tumors. These studies revealed, although with less substantial data, the presence of genetic and genomic alterations in the pathologically normal urothelium of patients also with NMI tumors.…”
mentioning
confidence: 99%
“…Similar detailed molecular analyses of pathologically normal sections of the bladder from patients with NMI tumors remains scarce, as these patients rarely are subjected to cystectomy. However, Thomsen et al 9 and Strandgaard et al 10 approached the problem by multiple sampling of tumor free regions of the urothelium from bladders with non-muscle invasive tumors. These studies revealed, although with less substantial data, the presence of genetic and genomic alterations in the pathologically normal urothelium of patients also with NMI tumors.…”
mentioning
confidence: 99%
“…Therefore, the architecture appears to predispose tissues to multiple origins of tumors. However, DNA sequence data usually suggest a process of single origin (Parsons 2008;Thirlwell, et al 2010;Lindberg, et al 2013;Ma, et al 2017;Wei, et al 2017;Cross, et al 2018;Parsons 2018;Strandgaard, et al 2019). This study aims to resolve this apparent contradiction.…”
Section: Introductionmentioning
confidence: 88%
“…Given l = n x e < 0.1, e is extremely small, determined by the gradual accumulation of advantageous mutations that drive tumorigenesis. The probability of having more than 2 independent tumors should thus be negligible (Parsons 2008;Thirlwell, et al 2010;Lindberg, et al 2013;Ma, et al 2017;Wei, et al 2017;Parsons 2018;Strandgaard, et al 2019). This is true even when multiple nodules are observed as they usually result from metastasis (Cresswell, et al 2020;Hu, et al 2020).…”
Section: Sampling Considerations For Testing the Theorymentioning
confidence: 99%
“…Next generation sequencing technologies are allowing the detection of mutations present in small areas of tissue at an unprecedented level of resolution, thus being suitable tools to characterize field changes in the urothelium. In this issue, Strandgaard et al [3] perform deep-targeted amplicon sequencing of paired samples of tumor and histologically normal-appearing urothelium from four patients with advanced bladder cancer treated with radical cystectomy. The small cohort comprises two individuals with multifocal disease and two with unifocal disease.…”
mentioning
confidence: 99%
“…Three types of mutations are identified by Strandgaard and colleagues [3]: T-mutations, found exclusively in the tumor; S-mutations, found both in tumor and non-neoplastic urothelium; and Nmutations, found exclusively in non-neoplastic samples (hereafter referred to as normal tissue). The two former types are more abundant.…”
mentioning
confidence: 99%